Dispersion of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) in kale and cabbage fields - da Silva Ponce, Franciely; Oliveira , Moisés Daniel de; de Lima Toledo , Claudia Aparecida; Alves de Oliveira , Lucas; Monesi da Silva , Willian Ricardo; Seabra Júnior , Santino; de Oliveira , Regiane Cristina (Comunicata Scientiae, 2022)
Parasitoids of the Trichogramma genus are used worldwide for pest management. The ability to disperse these insects in crops determines the number of release points necessary for there to be satisfactory results in terms of parasitism and, consequently, pest management. To determine the dispersal capacity of T. pretiosum in cabbage and cabbage crops, 26 x 26 m areas were demarcated, in which cards containing A. kuehniella eggs were placed, distributed in a concentric and equidistant manner. In the center of each area, 100,000 parasitoids were released and parasitism was allowed for 24 hours. The experimental design used was in randomized blocks, with five treatments (distance) and four replications. The average dispersed distance was 6.27 meters in cabbage and 6.07 in cabbage, while the dispersion area was 81.23 in cabbage cultivation and 79.03 meters in cabbage cultivation. 123 release points required for kale and 126 for cabbage.